Electronic Evidence and Digital Criminalisation in the 17 + 8 People’s Demands Demonstration - Wijaya, Emilia Metta Karunia (Law Research Review Quarterly, 2025)
This article examines the role of electronic evidence and the practice of digital criminalisation in the series of demonstrations of 17+8 people's demands. The purpose of this study is to analyse the position of electronic evidence in proving criminal acts in the series of protests 17+8 of people's needs, the application of the ITE Law to the digital activities of the 17+8 demonstrations in the context of digital criminalisation, and the adequacy of legal norms in protecting freedom of expression in the digital era. The research uses a normative juridical method with a case approach to examine the practice of digital criminalisation that occurred in a series of demonstrations. The results show that electronic evidence has been recognised as legal evidence and plays a strategic role in ensuring public accountability, but its implementation is ambivalent. The multi-interpretive articles in the ITE Law are often used selectively against demonstrators, thus strengthening the pattern of digital repression. On the other hand, although Indonesia's legal norms are relatively complete, their implementation is still weak and emphasises public order over protecting people's fundamental rights. This article recommends reformulating the ITE Law's rubber articles, strengthening the PDP Law's implementation, and establishing an independent institution to oversee the protection of personal data and digital restrictions.